BMP signaling in telencephalic neural cell specification and maturation - Gámez, Beatriz; Rodriguez-Carballo, Edgardo; Ventura, Francesc (Frontiers in Cellular Neuroscience, 2013)
Bone morphogenetic proteins (BMPs) make up a family of morphogens that are critical for patterning, development and function of the central and peripheral nervous system. Their effects on neural cells are pleiotropic and highly dynamic depending on the stage of development and the local niche. Neural cells display a broad expression profile of BMP ligands, receptors and transducer molecules. Moreover, interactions of BMP signaling with other incoming morphogens and signaling pathways are crucial for most of these processes. The key role of BMP signaling suggests that it includes many regulatory mechanisms that restrict BMP activity both temporally and spatially. BMPs affect neural cell fate specification in a dynamic fashion. Initially they inhibit proliferation of neural precursors and promote the first steps in neuronal differentiation. Later on, BMP signaling effects switch from neuronal induction to promotion of astroglial identity and inhibition of neuronal or oligodendroglial lineage commitment. Furthermore, in postmitotic cells, BMPs regulate cell survival and death, to modulate neuronal subtype specification, promote dendritic and axonal growth and induce synapse formation and stabilization. In this review, we examine the canonical and non-canonical mechanisms of BMP signal transduction. Moreover we focus on the specific role of BMPs in the nervous system including their ability to regulate neural stem cell proliferation, self-renewal, lineage specification and neuronal function.